General geometric levy processes for asset prices modelling - Önalan, Ömer (İktisadi ve İdari Bilimler Dergisi, 2004)
In this study, the stock prices process is modelled by stochastic differential equation driven by a general Lévy process. We review some fundemental mathematics proporties of Lévy distribution.
Keywords: levy processes, Market models, Martingales, Arbitrage, Option pricing